Repression of JAK2-STAT1 and PD-L1 by CEP-33779 ameliorates the LPS-induced decline in phagocytic activity of alveolar macrophages and mitigates lung injury in mice - Wang, Yu-Han; Li, A-Guo; Wang, Hong-Yan; Tu, Yong-Sheng (Frontiers in Immunology, 2024)
BackgroundThe role of the JAK2-STAT1/PD-L1 pathway in the phagocytic activity of alveolar macrophages (AMs) during LPS-induced acute lung injury in mice remains poorly understood. This study aims to explore whether the JAK2-STAT1/PD-L1 pathway is upregulated on AMs in LPS-induced mice acute lung injury and to further explore the impact of the JAK2-specific inhibitor CEP-33779 on the LPS-induced impairment of AMs phagocytic activity and lung injury.MethodsALI was induced in mice via intratracheal administration of LPS, followed by intragastric administration of JAK2 inhibitor CEP-33779 suspension. Immunohistochemistry was conducted to assess PD-L1 expression in lung tissue, as well as p-JAK2, p-STAT1, and PD-L1 expression on AMs in bronchoalveolar lavage fluid (BALF) using immunofluorescence. Levels of TNF-α and IL-6, as well as protein concentration in BALF, were measured using enzyme-linked immunosorbent assay and Bicinchoninic acid assays, respectively. Hematoxylin-eosin staining and lung injury score were employed to evaluate pathological changes in mouse lungs. Total cell count in BALF was determined using a cell counter. Furthermore, western blot and immunofluorescence was conducted to assess the effect of JAK2 and STAT1 inhibitor on JAK2-STAT1 pathway activation and PD-L1 expression, while confocal microscopy with latex beads rabbit IgG FITC complex was used to observe MH-S cells phagocytic ability.ResultsThe study revealed that LPS stimulation triggered the activation of the JAK2-STAT1 pathway and an upregulation of PD-L1 on AMs in both LPS-induced acute lung injury mice and MH-S cell lines. Moreover, treatment with the JAK2 and STAT1 inhibitor effectively reduced the activation of JAK2-STAT1 signaling, downregulated PD-L1 expression on AMs in BALF from LPS-induced ALI mice and LPS-stimulated MH-S cells, and significantly improved the LPS-induced reduction in phagocytic activity in MH-S cells. Most notably, CEP-33779 treatment significantly mitigated the pulmonary inflammatory response and lung injury in mice with LPS-induced ALI.ConclusionsCollectively, these findings imply that the JAK2-STAT1 pathway plays a role in the upregulation of PD-L1, which in turn is associated with the diminished phagocytic activity in LPS-induced AMs as well as lung injury. Furthermore, our study highlights that CEP-33779 treatment can effectively improve the reduced phagocytic activity of AMs and relieve lung injury induced by LPS through suppression of the JAK2-STAT1/PD-L1 pathway.